2021
DOI: 10.2147/prbm.s309806
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Anxiety and the Coping Strategies in the Southeast Ethiopia

Abstract: Background:The pandemic of coronavirus disease spreading is impacting mental health globally. Even though the pandemic is challenging for patients, the community, policymakers, as well as health organizations, and teams, the data on COVID-19 and its association with anxiety and coping mechanisms towards infection among community members are currently limited. Thus, the study is intended to assess COVID-19-related levels of anxiety and coping strategies among community members of Bale and East Bale Zones, South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Further, the study in China evaluated COVID-19-related anxiety using Generalized Anxiety Disorder Scale. Contrary to this, a study conducted in Southeast Ethiopia (16.58%) among residents of the community aged 18 years and above [ 37 ], and in Turkey (13.63%) among university students [ 38 ] reported lower findings.…”
Section: Discussionmentioning
confidence: 77%
“…Further, the study in China evaluated COVID-19-related anxiety using Generalized Anxiety Disorder Scale. Contrary to this, a study conducted in Southeast Ethiopia (16.58%) among residents of the community aged 18 years and above [ 37 ], and in Turkey (13.63%) among university students [ 38 ] reported lower findings.…”
Section: Discussionmentioning
confidence: 77%
“…However, most studies reported that females tend to avoid healthcare during the pandemic (Jiskrova et al, 2021; Kang, 2013; Yunus et al, 2021). Women were more likely to have suffered from anxiety and insomnia during the pandemic (Wong et al, 2020) and more likely to experience unmet healthcare needs than men (Kim et al, 2021) which may, in turn, have been affected by strategies employed to cope with the pandemic (Teferu Engida et al, 2021).…”
Section: Discussionmentioning
confidence: 99%